Orthopedic Manifestations of Spinal Muscular Atrophy: Clarified and Unresolved Theoretical and Practical Issues - Zyma, A.M.; Huk, Yu.M.; Smaha, A.V.; Vatamanesku, L.I.; Cheverda, A.I.; Kincha-Polishchuk, T.A.; Skuratov , O.Iu. (TERRA ORTHOPAEDICA, 2025)
Summary. Spinal muscular atrophy (SMA) is an autosomal recessive disorder characterized by progressive weakness and muscle atrophy resulting from degeneration of neurons in the spinal and bulbar parts of the brain. Objective. This study aims to analyze the literature devoted to the diagnosis and treatment of orthopedic pathologies in patients with various forms of SMA. Materials and Methods. The study is based on a retrospective review of articles focused on the diagnosis and treatment of patients with SMA. The PubMed database was searched for articles published between 2010 and 2024, with a focus on materials from the last five years. Results and Discussion. The literature search on musculoskeletal pathologies in SMA revealed a limited number of studies addressing the clinical and orthopedic manifestations of SMA and their dependence on the type of disease. There is practically no information on changes in the structural and functional state of bone tissue and muscle structures in patients with SMA. No unified classification has been found that defines the impairment of the functional state of the lower extremities depending on the muscle strength deficit, the type of orthopedic manifestations, and the degree of loss of function affecting independent movement. The analysis of the literature indicates a lack of consensus regarding surgical strategies for the treatment of orthopedic manifestations of SMA; the features of surgical interventions for the correction of certain orthopedic manifestations are also not covered, and a system for medical correction of disorders in the structural state of the bone system in SMA has not been developed. Conclusions. The pathology of the musculoskeletal system in SMA requires a detailed fundamental study considering the type of disease, its progression, the condition of muscle and bone structures, patient age, the type and severity of orthopedic pathology, while the methods used for its correction require further development and improvement.